2020
DOI: 10.3390/polym12081773
|View full text |Cite
|
Sign up to set email alerts
|

Acrylic Bone Cements Modified with Graphene Oxide: Mechanical, Physical, and Antibacterial Properties

Abstract: Bacterial infections are a common complication after total joint replacements (TJRs), the treatment of which is usually based on the application of antibiotic-loaded cements; however, owing to the increase in antibiotic-resistant microorganisms, the possibility of studying new antibacterial agents in acrylic bone cements (ABCs) is open. In this study, the antibacterial effect of formulations of ABCs loaded with graphene oxide (GO) between 0 and 0.5 wt.% was evaluated against Gram-positive bacteria: Bacillus ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 55 publications
(73 reference statements)
2
22
0
Order By: Relevance
“…On the other hand, according to the results presented by Paz et al [114], ABCs modified with 0.1 wt.% of GO showed a lack of antimicrobial activity against S. Aureus, possibly because the GO powder level was below the threshold required for a positive antimicrobial response. This confirms the results obtained by several authors, who affirmed that GO's antibacterial activity depends on the concentration [108,163,164]. Table 4 shows a summary of the strategies used to confer antimicrobial activity to bone cements and the characteristics offered by CS and GO.…”
Section: Antibacterial Effect Of Go On Abcssupporting
confidence: 88%
See 3 more Smart Citations
“…On the other hand, according to the results presented by Paz et al [114], ABCs modified with 0.1 wt.% of GO showed a lack of antimicrobial activity against S. Aureus, possibly because the GO powder level was below the threshold required for a positive antimicrobial response. This confirms the results obtained by several authors, who affirmed that GO's antibacterial activity depends on the concentration [108,163,164]. Table 4 shows a summary of the strategies used to confer antimicrobial activity to bone cements and the characteristics offered by CS and GO.…”
Section: Antibacterial Effect Of Go On Abcssupporting
confidence: 88%
“…The addition of GO in percentages up to 0.5 wt.% in ABCs has favored bending and compression [107][108][109][110]. Paz et al [110] reported increased fracture toughness and fatigue performance attributed to the GO, induced deviations in the crack fronts, and hampered crack propagation.…”
Section: Bioactivity In Acrylic Bone Cements Loaded With Graphene Oxidementioning
confidence: 99%
See 2 more Smart Citations
“…Irrespective of the PG loading shown in ( Table 1 ), in some instances, the pores penetrate deep into the fibre [ 47 ]. The surface pores are therefore beneficial in exposing the PG layers to the environment, which is useful in antimicrobial applications [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%